Content Analysis of Food and Beverage Advertisements on TV, Radio, and Billboards in Iran - Maryam Amini PhD; Delaram Ghodsi PhD; Mehrnoosh Shafaatdoost MSc; Mohadese Borazjani MSc; Maryam Aghayan MSc; Nastaran Shariatzadeh BSc (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Food advertising may influence food preferences and consumption. Due to these advertisements’ role in health, the present study has updated the data available on television and radio food advertisements in Iran until 2020. Meanwhile, food advertisements on billboards have been analyzed for the first time. All programs broadcast on two TV and radio channels were downloaded and saved 24 h daily for one week (November 10-16th, 2020). Also, on November 15th billboards located on the busy highways of Tehran were photographed. Validated protocols analyzed the advertisements. A total of 6026 advertisements were analyzed, including 4287 on TV, 1545 on radio, and 194 on billboards. The total duration of TV and radio advertising was 48.6 h. Food products were the most displayed advertisements on TV, radio, and billboards (33.6%). Overall, “condiments” and “desserts” were the most frequently advertised food products among all the studied media (20% and 17%, respectively). The most common advertising appeal included “High quality” on TV and billboards and “Stimulation of profiteering and profit-seeking” on the radio. Advertising violation based on Iran’s regulations, Nutrient profile model for the marketing of food and non-alcoholic beverages to children in the WHO Eastern Mediterranean Region, and International Network for Food and Obesity / Non-communicable Diseases (NCDs) Research Monitoring and Action Support (INFORMAS) was reported to be 13%, 74%, and 51%, respectively. Food products ranked the highest among all the advertisements. A clear violation of domestic and international advertising regulations was observed which given the high share of food advertising in the studied media, could endanger public health. This study supports the need for stricter regulations and adherence to international standards to improve nutritional status.